Morphology and potential antibacterial capability of Actinoptychus octonarius Ehrenberg (Bacillariophyta) isolated from Manzanillo, Colima, in the Mexican Pacific coast. - Zatarain-Palacios, R.; Quijano-Scheggia, S.; Gaytán-Hinojosa, M. A.; Parra-Delgado, H.; Salas-Marias, N.; Dagnino-Acosta, A.; Ceballos-Magaña, S. G.; Muñiz-Valencia, R. (Revista Bio Ciencias, 2020)
Diatoms are ubiquitous in all aquatic areas. Recently, these marine microorganisms gained attention because of their health benefits, especially when addressing the problem of antibiotic resistance. In this study, Actinoptychus octonarius Ehrenberg was identified by its ultrastructural details by Scanning Electron Microscopy (SEM). Additionally, the antibacterial properties of A. octonarius Ehrenberg were evaluated employing the method of disk diffusion against Staphylococcus aureus and Vibrio vulnificus bacteria. Four A. octonarius Ehrenberg extracts were obtained by the sequential multi-solvent extraction process using hexane, dichloromethane, methanol, and water. The best antibacterial activity was observed for the methanol extract, which had a significant effect against S. aureus and V. vulnificus. Hexane extracts showed a limited antibacterial activity only against S. aureus and showing no significant effects against V. vulnificus. The area of inhibition of the extracts was higher to 1 cm2. The aqueous and dichloromethane extracts did not present antibacterial activity. In summary, this study revealed, for the first time, morphological characteristics of A.octonarius Ehrenberg diatom through a SEM methodology. Furthermore, it was observed that molecules present in the methanolic extracts of A. octonarius Ehrenberg have antibacterial action against Gram-positive S. aureus and Gram-negative V. vulnificus., while the hexane extract showed effect only against V. vulnificus.